Postcolonial Literatures and Deleuze
IX, 220 p.
Keywords: Bringing together high profile scholars in the fields of Deleuze and postcolonial studies, this book highlights the overlooked connections between two major schools of contemporary criticism and establishes a new critical discourse for postcolonial literature and theory.